The Human Foot A Companion to Clinical Studies - Klenerman, Leslie; Wood, Bernard (Springer London : Imprint: Springer, 2006)
The Human Foot, a collaboration between an orthopedic surgeon and a paleoanthropologist, starts by tracing the evolutionary history of feet all the way from their beginnings as fins to modern human feet. It presents the foot, a neglected but important region, taking into account advances in the study of evolution, imaging, physiology and biomechanics. The development of gait in children is described and measurements of foot pressures and their value are discussed. Also analyzed are various examples of the foot in action such as running, ballet dancing, tightrope walking, kicking, firewalking, swimming and the foot in microgravity, ending with a chapter on the loss of parts and the whole of the foot, the consequences and prosthetic replacement. The text is an invaluable resource for orthopedic surgeons, physiotherapists, sports scientists, and podiatrists.